Answer:
f (-1) = -3
f (0) = 10
f (2) = 26
Step-by-step explanation:
The given function is a piece-wise function. This means that we choose the equation to substitute in based on the given value of x (the input)
We are given that:
If the value of x is less that 0, then the function is:
f(x) = 8x + 5
If the value of x is equal to or more than 0, then the function is:
f(x) = 8x + 10
Now, let's check the required values:
a. f(-1): The given value of x is less than 0, so we substitute in the first equation
f(-1) = 8x + 5 = 8(-1) + 5 = -3
b. f(0): The value of x is equal to 0, so we substitute in the second equation
f(0) = 8x + 10 = 8(0) + 10 = 10
c. f(2): The value of x is more than 0, so we substitute in the second equation
f(2) = 8x + 10 = 8(2) + 10 = 26
Hope this helps :)